Eficacia del fortalecimiento del suelo pélvico para la incontinencia urinaria en post prostatectomía, revisión sistemática - Onofa Tupiza, Madeline Julissa (2020)
OBJETIVE: The aim is to perform a systematic review on the efficacy of pelvic floor reinforcement for post-prostatectomy urinary incontinence. MATERIALS AND METHODS: The PubMed, ScienceDirect, Scholar Academic databases were used to search for experimental articles. In this study, 39 articles were found, of which 8 post-prostatectomy articles were included, which were selected because within the protocol there was pelvic floor muscle training We also collected 4 articles of pre and post prostatectomy that present a comparison between patients who perform a preoperative and postoperative program with pelvic floor training. Finally, 27 articles were excluded because they did not have a good population, another was mention of various types of medical treatments such as transplants and excluded the systematic reviews. RESULTS: Of the 8 articles analyzed (Annex 1) for post prostatectomy pelvic training, 7 articles reported significant results in early recovery from urinary incontinence in terms of measuring the use of pads, improvement in quality of life and early recovery from continence after training, and only 1 of the articles presented insignificant results. On the other hand, of the 4 articles analyzed (Annex 2) of preoperative pelvic training, two of these articles reported a higher percentage of patients who recovered continence and two articles registered non significant results. CONCLUSIONS: There is scientific evidence that shows that pelvic floor muscle training exercises practiced in pre and post RP for the recovery of continence, improves the quality of life and reduces the use of pads. KEY WORDS: Prostatectomy, urinary incontinence, post prostatectomy, pelvic floor reinforcement, pelvic floor training, pelvic floor.